Advanced engineering analysis the calculus of variations and functional analysis with applications in mechanics - Lebedev, L. P. (World Scientific Pub. Co., 2012)
Advanced Engineering Analysis is a textbook on modern engineering analysis, covering the calculus of variations, functional analysis, control theory, as well as applications of these disciplines to mechanics. The book offers a brief and concise, yet complete explanation of essential theory and applications. It contains exercises with hints and solutions, ideal for self-study